2018
DOI: 10.1186/s12889-018-5520-8
|View full text |Cite
|
Sign up to set email alerts
|

A pedometer-based walking intervention with and without email counseling in general practice: a pilot randomized controlled trial

Abstract: BackgroundGeneral practitioners play a fundamental role in combatting the current epidemic of physical inactivity, and pedometer-based walking interventions are able to increase physical activity levels of their patients. Supplementing these interventions with email counseling driven by feedback from the pedometer has the potential to further improve their effectiveness but it has to be yet confirmed in clinical trials. Therefore, the aim of our pilot randomized controlled trial is to evaluate the feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
0
15
0
2
Order By: Relevance
“…The qualitative study was conducted alongside a 12-week pedometer-based walking intervention with email counseling in physically inactive adults recruited from four general practices. Details of the intervention design and its outcomes have been reported elsewhere (Vetrovsky et al, 2018). Briefly, the participants were instructed to wear the pedometer daily, check the step count every evening, and gradually increase the daily number of steps up to 10,000.…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative study was conducted alongside a 12-week pedometer-based walking intervention with email counseling in physically inactive adults recruited from four general practices. Details of the intervention design and its outcomes have been reported elsewhere (Vetrovsky et al, 2018). Briefly, the participants were instructed to wear the pedometer daily, check the step count every evening, and gradually increase the daily number of steps up to 10,000.…”
Section: Methodsmentioning
confidence: 99%
“…In healthy populations, consumer-level activity monitors (i.e. pedometers and accelerometers) are frequently used as motivational tools to increase PA [68] and many of them have been previously shown to be valid devices for assessing daily step count both in lab-based and free-living settings [911]. However, since those validation studies were conducted in healthy volunteers and didn’t examine the validity of the devices at slower walking speeds, it is not clear whether their results can be applied to patients with HF, who typically walk at slower speeds and shuffle their feet [12].…”
Section: Introductionmentioning
confidence: 99%
“…This is a very important factor because low adherence can hinder what would be an otherwise well-designed intervention. Vetrovsky et al (2018) found 83% pedometer wear adherence and Cadmus-Bertram et al (2015) found 80%, however, neither of these studies were focused on an older adult population per se. The comparatively high adherence levels observed in our study indicate that the 1.5-hour study orientation/technology training session, which emphasized good practices for remembering to wear the pedometer and completing the daily surveys, was an effective tool for increasing adherence.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, retention in our trial (83%) was similar to Buman et al (2011), who observed an 85% retention rate at the end of the trial and follow-up at 18 months was 61%. Vetrovsky et al (2018), on the other hand, reported 100% retention. However, this may be explained by their pre-randomization procedure that demanded patients to upload their pedometer data to a website prior to randomization, which 27% failed to do.…”
Section: Discussionmentioning
confidence: 96%